Pengaruh Atribut Produk Salad Wrap terhadap Keputusan Pembelian Konsumen di Healthy Food Restaurant Fit Fuel Salad & Smoothies Bar Kota Bandung - Imana, Salsabila Iftikhar; Rochdiani, Dini; Mukti, Gema Wibawa; Fatimah, Sri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Fit Fuel Salad & Smoothies Bar is a restaurant that offers various healthy food menus. This study aims to (1) assess the product attributes of salad wraps at Fit Fuel Salad & Smoothies Bar from the consumer's perspective and (2) analyze the influence of these product attributes on purchasing decisions at Fit Fuel Salad & Smoothies Bar. The research method used in this study is quantitative. A sample size of 97 was drawn through accidental sampling due to the large population size, focusing on consumers who have purchased salad wraps from Fit Fuel Salad & Smoothies Bar. The results of this study show that the product attributes and purchasing decisions of salad wraps at Fit Fuel Salad & Smoothies Bar are considered good by consumers. The product attributes significantly influence the purchasing decision of salad wraps at Fit Fuel Salad & Smoothies Bar, with an influence rate of 59.5%, while the remaining 40.1% is influenced by other factors not observed in this study. Evaluation recommendations suggest that the restaurant should pay attention to and improve the product attributes of salad wraps, which can be implemented in other products to effectively increase sales and reach more consumers.